(untitled) (International journal of medical sciences, 2026)
Liver involvement is a frequent but often underrecognized manifestation in systemic lupus erythematosus (SLE). The aim of this study was to determine the prevalence, etiological spectrum, clinical-laboratory correlations, diagnostic challenges, and outcomes of liver damage in a cohort of SLE patients. This retrospective observational cohort study included 87 adult SLE patients with documented liver function test abnormalities from a rheumatology-hepatology referral center. Data were collected on demographics, SLE activity (SLEDAI-2K), laboratory parameters, medication history, imaging, and liver biopsy results (available in 38 patients). Etiological diagnosis was assigned by consensus of a rheumatologist and hepatologist after exclusion of alternative causes. Statistical analysis included descriptive statistics, group comparisons, and multivariate logistic regression. Liver involvement was detected in 27.9% of screened SLE patients. The median age was 38 years (IQR 29–47), with female predominance (94.3%). The most common etiologies were drug-induced liver injury (39.1%, mainly methotrexate and azathioprine), lupus hepatitis (20.7%), autoimmune hepatitis overlap (13.8%), and non-alcoholic fatty liver disease (12.6%). Most cases presented with mild asymptomatic transaminitis (78.2%). Liver biopsy showed macrovesicular steatosis (68.4%), lobular inflammation (55.3%), and mild interface hepatitis (42.1%); advanced fibrosis/cirrhosis occurred exclusively in the AIH-SLE overlap group. Lupus hepatitis was associated with higher SLEDAI scores (median 14 vs. 8, p=0.002) and anti-ribosomal P positivity (38.9% vs. 9.1%, p=0.011). Drug-induced cases had higher cumulative glucocorticoid exposure and high reversibility after drug withdrawal (88.2%).